Symmetrical couple f-shaped notches with high rejection c-band of uwb patch antenna - Abdulhasan, Raed Abdulkareem; Ramli, Khairun Nidzam; Alias, Rozlan; Hamzah, Shipun Anuar; Audah, Lukman; Salh, Adeeb; O. Mumin, Abdulrashid; Jawhar, Yasir Amer (Praise Worthy Prize, 2017)
The ultra-wideband (UWB) antenna is developed to cover a broad bandwidth. ‎The UWB radio systems are interfered ‎by the ‎same ‎spectrum ‎that shared with the local bands. In this paper, two F-shaped slots on a hexagonal patch UWB antenna are demonstrated ‎‎ to realize a high band rejection. The symmetrical couple F-slots is ‎notched on the hexagonal UWB ‎ ‎patch antenna to avoid the interference ‎and ‎‎enhance the notching results at C-band. The demonstrated ‎antenna employs a coplanar waveguide ‎(CPW) technique to meet a fractional bandwidth of 126%. The proposed method validates ‎several ‎‎reconfigurations of the F-slot location on the demonstrated design. Six steps ‎parametric study are considered to test the slots location. The results of the proposed antenna with slots are introduced based on analytical, simulation, and ‎measurement. The total design size ‎‎28 mm × 43 mm × 1.6 ‎mm is simulated by ‎using CST Microwave Studio. The two F-slots are achieved the antenna gain of -6 dB, ‎return loss of -1.2 ‎dB, and ‎VSWR of 15.2 at the rejected band of 4 GHz. The ‎measurement results are compared with the simulation results between the three ‎prototypes. The current ‎distribution on the design is discussed at 2.88 GHz and 4 GHz frequencies. The radiation patterns illustrate ‎omnidirectional of H-plane and bidirectional of E-plane. This paper validates the slots locations to enhance the notches performance and reduce the interference.